IMPACT OF ELECTRONIC BANKING INSTRUMENTS ON THE INTERMEDIATION EFFICIENCY OF THE NIGERIAN ECONOMY - Okoro A. S. Ph.D (International Journal of Accounting Research, 2013)
This study examined the impact of selected e-payment instruments on the intermediation efficiency of the Nigerian economy. Using time series data of 2006 – 2011 the study employed multiple regression technique in the analysis of the sourced data. Employing intermediation efficiency indicator (the ratio of currency outside bank to broad money supply) as a dependent variable, while the automated teller machine (ATM), point of sales (PoS), Mobile and Internet service values were used as the independent variables, the following findings were made: that there is significant relationship between ATM, PoS, Internet service values and the intermediation efficiency of the of Nigerian economy. However, the study also reviles that there is no significant relationship between Mobile service value and intermediation efficiency of the Nigerian economy within the period under study. The implication of these finding is that the ATM, PoS and Internet services are the major instruments used by the customers of the deposit money banks in Nigeria, may be as a result of the level of awareness created by the banks in Nigeria. On the other hand the insignificant contribution of the Mobile service value to intermediation efficiency may be as a result of the user’s ignorance or the banks’ insufficient effort in selling the product effectively. Further more the result implies that the higher the usage of the selected e-payment instruments in Nigeria the better the intermediation efficiency of the Nigerian economy. Therefore this study recommends that the banks should put more effort in advertising these products in Nigeria. Improved internet and information technology awareness for the public in form of seminars and conferences will cause an upswing in e-payment techniques usage. This may cause a positive impact on the usage of these instruments by the customers of the deposit money banks in Nigeria and hence improve the intermediation efficiency of the Nigerian economy.